Cerebrovascular disease promotes tau pathology in Alzheimer's disease. Issue 2 (19th August 2020) - Laing, Krystal K; Simoes, Sabrina; Baena-Caldas, Gloria P; Lao, Patrick J; Kothiya, Milankumar; Igwe, Kay C; Chesebro, Anthony G; Houck, Alexander L; Pedraza, Lina; Hernández, A Iván; Li, Jie; Zimmerman, Molly E; et al.
Abstract: Small vessel cerebrovascular disease, visualized as white matter hyperintensities on T2-weighted magnetic resonance imaging, contributes to the clinical presentation of Alzheimer's disease. However, the extent to which cerebrovascular disease represents an independent pathognomonic feature of Alzheimer's disease or directly promotes Alzheimer's pathology is unclear. The purpose of this study was to examine the association between white matter hyperintensities and plasma levels of tau and to determine if white matter hyperintensities and tau levels interact to predict Alzheimer's disease diagnosis. To confirm that cerebrovascular disease promotes tau pathology, we examined tau fluid biomarker concentrations and pathology in a mouse model of ischaemic injury. Three hundred ninety-one participants from the Alzheimer's Disease Neuroimaging Initiative (74.5 ± 7.1 years of age) were included in this cross-sectional analysis. Participants had measurements of plasma total-tau, cerebrospinal fluid beta-amyloid, and white matter hyperintensities, and were diagnosed clinically as Alzheimer's disease ( n = 97), mild cognitive impairment ( n = 186) or cognitively normal control ( n = 108). We tested the relationship between plasma tau concentration and white matter hyperintensity volume across diagnostic groups. We also examined the extent to which white matter hyperintensity volume, plasma tau, amyloid positivity status and the interaction between white matter hyperintensities and plasma tau correctly classifies diagnostic category. Increased white matter hyperintensity volume was associated with higher plasma tau concentration, particularly among those diagnosed clinically with Alzheimer's disease. Presence of brain amyloid and the interaction between plasma tau and white matter hyperintensity volume distinguished Alzheimer's disease and mild cognitive impairment participants from controls with 77.6% and 63.3% accuracy, respectively. In 63 Alzheimer's Disease Neuroimaging Initiative participants who came to autopsy (82.33 ± 7.18 age at death), we found that higher degrees of arteriosclerosis were associated with higher Braak staging, indicating a positive relationship between cerebrovascular disease and neurofibrillary pathology. In a transient middle cerebral artery occlusion mouse model, aged mice that received transient middle cerebral artery occlusion, but not sham surgery, had increased plasma and cerebrospinal fluid tau concentrations, induced myelin loss, and hyperphosphorylated tau pathology in the ipsilateral hippocampus and cerebral hemisphere. These findings demonstrate a relationship between cerebrovascular disease, operationalized as white matter hyperintensities, and tau levels, indexed in the plasma, suggesting that hypoperfusive injury promotes tau pathology. This potential causal association is supported by the demonstration that transient cerebral artery occlusion induces white matter damage, increases biofluidic markers of tau, and promotes cerebral tau hyperphosphorylation in older-adult mice. Abstract : Plasma-derived total-tau concentration is highly correlated with WMH volume, an MRI marker of small vessel ischaemic damage, particularly among individuals with clinical Alzheimer's disease. A parallel mouse model confirmed white matter damage, hyperphosphorylated tau pathology and elevated tau concentration in plasma and CSF due to surgically induced ischaemic injury. Graphical Abstract: